LATERAL VARIATIONS IN THE CHEMISTRY OF ROCK-FORMING MINERALS IN THE BACKARC ZONE OF THE KURIL ISLANDS: AMPHIBOLES - Osipenko A.B. (My University, 2000)
This study of the lateral chemical variations of amphiboles from phenocrysts in the andesites of submarine volcanoes located on the Sea of Okhotsk slope of Iturup Island, Kuril Island Arc, did not reveal any significant variations in the mineral chemistry that could be related to the spatial location or geochemical trend of the enclosing rocks. A difference between a petrochemical and a mineral (amphibole) zonal pattern is believed to have been caused by differences in the factors that had caused a spatial heterogeneity of the parental andesite magma and particular physicochemical conditions of its evolution in the magma source. Data on the main variation trend of the amphibolite composition suggest that the main controlling factors had been the temperature and oxidation-reduction conditions of the andesite crystallization. The results of this study can be explained by the local evolution of the physicochemical conditions of andesite magma crystallization in an isolated chamber.